Test on Diaphragm Behavior of Dry-Floor System with Steel-Edged Gypsum Planks - Jeng Fang, Pen (Engineering Journal, 1968)
The U. S. Steel Corporation and the U. S. Gypsum Company have cooperated in testing a lightweight "dry" steel-edged gypsum-plank floor system for steelframed apartment buildings. Less dead weight, reduced construction time, and all-weather installation are the chief advantages of the dry floor. In actual service, floors, in addition to meeting the performance criteria with regard to vertical loading, sound transmission, and fire resistance, can also act as diaphragms distributing lateral loads from unbraced areas into braced frames. Although the diaphragm behavior of monolithic and uniform floors is relatively easily predicted by analysis, the gypsum-plank floor, being a complex composite system, cannot be easily analyzed. Therefore, a series of diaphragm tests was conducted on a full-scale floor system, and the result is reported herein. Although specific details had to be selected for the steel frame and plank floor specimen, it is recognized that other details may be more advantageous in particular building applications. The degree to which the test results apply to floors using such other details is a matter of judgement and cannot be ascertained in a general manner.